HIGH SCHOOL TEACHER TRAINING TO IMPROVE THE SCIENTIFIC WRITING PROFESSIONALISM - Saputra, Eri; Mirsa, Rinaldi; Muhammad, Muhammad (Universitas Muhammadiyah Aceh, 2021)
Teachers are not only obliged to transfer knowledge to their students. However, they are required to be more professional and more competent. So one of the means to improve the ability of teachers in professional development is to increase the publication of scientific papers. However, based on observations and interviews with teachers of SMA Negeri 1 Syamtalira Aron, North Aceh Regency, there is still a lack of understanding regarding the publication of scientific writing, as well as the use of applications that can be designed as media in research. For this reason, it is very necessary to provide guidance, assistance for training for teachers as an effort to develop the skills and creativity of teachers in making scientific papers and introduction of applications so that they can be more varied. Activities that will be carried out during PKM for partners are: 1) coaching training in the use of software as a learning medium, scientific writing, and journal citation methods. 2) OJS training. 3) assistance in writing scientific papers. The method used in this service activity is persuasive-educative. The implementation phase in this activity consists of: site survey, planning, implementation, and evaluation. The highest average value in the material being taught where the value is 4.78 with a very good category. Participants were very interested in all the material taught by the presenters. While the lowest average value in responding to the questions given where the value is 4.41 with a very good category.Keywords: Writing, OJS, Learning Media